MENGEMBANGKAN KEBERSAMAAN ANTARBANGSA MELALUI BAHASA - Nurhayati Nurhayati (KAJIAN SASTRA, 2010)
Up to now, English is used as a communication language in ASEAN forum. To incourage the solidarity among the society in South East Asia, it is necessary to change the policy. The paper offers one alternative of using regional languages instead of English in the forum. Malay languages, those are Indonesian Malay, and Malay used in Malaysia, Brunei Darussalam, and Singapure are potential languages that can be used as a means of communication, especially among the four societies. To do that, we have to increase the mutual intelligibility among the four languages and to incourage the societies to use the four languages.